2023
DOI: 10.1007/s40519-023-01536-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a vegetarian diet combined with aerobic exercise on glycemic control, insulin resistance, and body composition: a systematic review and meta-analysis

Abstract: Background Vegetarian diets and aerobic exercise are increasingly accepted as a common way to improve lifestyle. Several studies have shown that vegetarian diets combined with aerobic exercise interventions have a significant effect on preventing and reducing the risk of metabolic diseases. Methods A search of the PubMed, EBSCO, Embase, CENTRAL, and Web of Science databases was conducted for comparative studies of pre- and post-vegetarian diet adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…Benatar et al [ 25 ]–including 12,619 vegans and 179,630 omnivores from 40 observation studies–and Dinu et al [ 14 ]–based on 19 cross sectional studies, for a total of 8,376 vegans and 123,292 omnivores–reported the same exact result, with a mean lower BMI in vegans vs omnivores, equal to -1.72 kg/m 2 (95%CI: -2.30, -1.16) and -1.72 kg/m 2 (95%CI: -2.21,-1.22; p<0.0001), respectively. The meta-analysis by Long et al [ 41 ], performed on 27 studies, reported a MD of -0.70 kg/m 2 (95%CI: -1.38, -0.01) for BMI in vegans vs. omnivores. A systematic review and meta-analysis by Agnoli et al [ 42 ] found mean BMI to be lower in subjects adhering to mixed vegetarian diets as compared to omnivores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benatar et al [ 25 ]–including 12,619 vegans and 179,630 omnivores from 40 observation studies–and Dinu et al [ 14 ]–based on 19 cross sectional studies, for a total of 8,376 vegans and 123,292 omnivores–reported the same exact result, with a mean lower BMI in vegans vs omnivores, equal to -1.72 kg/m 2 (95%CI: -2.30, -1.16) and -1.72 kg/m 2 (95%CI: -2.21,-1.22; p<0.0001), respectively. The meta-analysis by Long et al [ 41 ], performed on 27 studies, reported a MD of -0.70 kg/m 2 (95%CI: -1.38, -0.01) for BMI in vegans vs. omnivores. A systematic review and meta-analysis by Agnoli et al [ 42 ] found mean BMI to be lower in subjects adhering to mixed vegetarian diets as compared to omnivores.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis by Long et al [ 41 ], based of 27 cross sectional studies, showed a MD for homeostasis model assessment of insulin resistance -measured as HOMA-IR, a unitless measure ideally less than one- of -0.75 (95%CI: -1.08, -0.42), fasting plasma glucose in vegetarians who adhered also to an exercise intervention as compared to omnivores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Therefore, integrating exercise with a balanced diet can yield a synergistic metabolic response. 81 As an illustration, integrating RET with an energy-restricted high-protein diet may facilitate weight reduction, engender favorable alterations in body composition, and amplify functional physical performance in adults with obesity. 82 Such a combination also enhances glycemic control and CVD risk markers in overweight and individuals with obesity diagnosed with T2D.…”
Section: Combination Of Exercise and Nutritionmentioning
confidence: 99%
“…Em uma metanálise recente realizada por Long et al (2023), ao estudar a associação entre o consumo de dieta vegetariana e prática de atividade física, evidenciaram a importância da combinação de ambos, enfatizando a necessidade do programa de intervenções abrangentes no estilo de vida a toda comunidade, com incentivo a dieta vegetariana e prática de atividade física diária de intensidade moderada.…”
Section: Tratamento Não Farmacológico Da Resistência à Insulinaunclassified